2013
DOI: 10.1111/jce.12245
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Versus Surgical Ablation of Atrial Fibrillation After a Failed Initial Pulmonary Vein Isolation Procedure: A Randomized Controlled Trial

Abstract: In patients with PAF and PersAF after failed initial CA, SA is superior to CA for maintenance of sinus rhythm, although serious adverse event rate is significantly higher for SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 23 publications
2
62
1
3
Order By: Relevance
“…585,586,601,602 A meta-analysis of these and other observational studies demonstrated a significant improvement of arrhythmia-free survival for the VATS procedure (78.4 vs 53%; RR 1.54; 95% CI 1.50–2.14; I 2 = 0%; P <.0001), with a clearer benefit for patients with persistent AF. 603 Complications were three times more frequent in the VATS group, mostly due to pneumothorax and pleural effusion.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 90%
“…585,586,601,602 A meta-analysis of these and other observational studies demonstrated a significant improvement of arrhythmia-free survival for the VATS procedure (78.4 vs 53%; RR 1.54; 95% CI 1.50–2.14; I 2 = 0%; P <.0001), with a clearer benefit for patients with persistent AF. 603 Complications were three times more frequent in the VATS group, mostly due to pneumothorax and pleural effusion.…”
Section: Section 5: Strategies Techniques and Endpointsmentioning
confidence: 90%
“…Intraoperative ablation of atrial fibrillation (AF) has been predominantly performed as a concomitant antiarrhythmic procedure . Recently, however, clinical and scientific interests of both electrophysiologists and cardiac surgeons have led to a revival of this procedure, not only as a concomitant practice, but also as a stand‐alone therapy for AF . Patients with an advanced atrial electrical disease and those with multiple unsuccessful catheter‐based interventions are thought to be potential candidates for antiarrhythmic surgery .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, clinical and scientific interests of both electrophysiologists and cardiac surgeons have led to a revival of this procedure, not only as a concomitant practice, but also as a stand‐alone therapy for AF . Patients with an advanced atrial electrical disease and those with multiple unsuccessful catheter‐based interventions are thought to be potential candidates for antiarrhythmic surgery . While the optimal lesion pattern still remains a matter of debate, comparative studies have revealed the importance of left atrial ablations, including pulmonary vein (PV) isolation (PVI) .…”
Section: Introductionmentioning
confidence: 99%
“…Autonomic system plays an important role in the pathogenesis of AF, although the effectiveness of autonomic modification for treatment of AF remains controversial [29]. Randomized trials tested the concept of standalone epicardial ablation in patients mostly with permanent AF who had recurrent AF after traditional endocardial approach proved reasonable efficacy [30,31]. Catheter-free ablation is an active area of research with promising results [24][25][26][27].…”
Section: Preventing the Defectmentioning
confidence: 99%